Fatigue damage assessment of metal sandwich panels under four-point bending cyclic loading conditions. (November 2022) - Faidzi, M.K.; Abdullah, S.; Singh, S.S.K.; Abdullah, M.F.; Azman, A.H.; Correia, J.A.F.O.
Graphical abstract: Highlights: Dimple core configuration provide better structural integrity for sandwich panel. Moderate size of hemispherical dimple provides an optimum bonding strength. Large dimple size is vulnerable to experience an early delamination between the layer. Analysis onto dimple hotspot region provide sufficient data for damage plot modelling. Fatigue assessment via damage analysis provide essential data for dissimilar panel. Abstract: This paper aims to investigate the effects on metal sandwich panels with different dimple core designs using four-point bending simulation under constant and variable amplitude loading. A core design with cavity and porosity in the body structure was found to reduce the panel structural integrity. This would lead to unstable bonding between the panels and initiate an early delamination process. Sandwich panels consisting of AR500 as the outer layer and magnesium alloy AZ31B as the core material were simulated using dimples of different diameters and depths; 5.0 / 2.5 mm, 6.0 / 3.0 mm, 7.0 / 3.5 mm and 8.0 / 4.0 mm, at a range of 50 % to 90 % of maximum strength, based on the lowest material strength for cyclic loading. The results indicate that the highest fatigue damage of 85 % occurred at the effective region of the dimple area, where force was applied to the panel. A hemispherical dimple core 6.0 mm in diameter and 3.0 mm in depth produced a reduction of failure at the effective zone of more than 85 % and the regression coefficient was over 0.89. This illustrates that a large dimple size was vulnerable to early delamination failure at the dimple region.